2022
DOI: 10.1007/s11356-022-24604-2
|View full text |Cite
|
Sign up to set email alerts
|

Water consumption prediction and influencing factor analysis based on PCA-BP neural network in karst regions: a case study of Guizhou Province

Abstract: Water consumption prediction is an integral part of water resource planning and management. Constructing a highly precise water consumption prediction model is of great significance for promoting regional water resource planning and high-quality development of the socio-economy. This paper focuses on the case of the typical karst region in Guizhou Province in China. Based on data on water consumption and its influencing factors spanning 2000–2020, the principal component analysis method was applied to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Precipitation was shown to be the principal growth factor impacting grain output and to have a suppressive effect on grain production when the effects of temperature and precipitation on the TFP in agriculture were compared, which was in line with the findings of Yang et al [54]. The data analysis results revealed that, in contrast to the findings of other studies, the rise in temperature was accompanied by an increase in the agricultural TFP.…”
Section: Limitations and Implicationssupporting
confidence: 86%
“…Precipitation was shown to be the principal growth factor impacting grain output and to have a suppressive effect on grain production when the effects of temperature and precipitation on the TFP in agriculture were compared, which was in line with the findings of Yang et al [54]. The data analysis results revealed that, in contrast to the findings of other studies, the rise in temperature was accompanied by an increase in the agricultural TFP.…”
Section: Limitations and Implicationssupporting
confidence: 86%
“…The optimal water allocation amount obtained by the WAINM for each water use sector is determined by the water price, the unit loss of the penalty for exceeding water demand, the unit loss of opportunity loss for not meeting the water demand of the water use sector, and the CDFs of water use and supply. The water price and the unit loss of the penalty and opportunity loss can be determined by the market or by the government; It is difficult to predict regional water demand, because the influencing factors are complex and dynamic, and water demand prediction is full of challenges with greater uncertainty 48 , 49 . In the current study, considering the short and stable time series of industrial water demand in the study area, meanwhile, the number of newspapers the newsvendor purchased every day in the Newsvendor model was assumed to conform to a uniform distribution 35 37 , the demand for newspapers is uncertain, just like the uncertainty in the water demand of each water use sector in the water resources allocation model, therefore, the uniform distribution was chosen to express the uncertainties in water demand.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [22] used BP neural networks for carbon emission prediction at the macro-field with significant results, which indicates that neural networks also have very good performance in macro-field prediction and can replace statistical-based methods. As the demand for prediction accuracy increases, a single model cannot meet the demand, so more and more scholars study the combination of multiple models for prediction to improve accuracy.…”
Section: Prediction Methods Based On Bp Neural Networkmentioning
confidence: 99%
“…Machine Dominance Limitations [22] Multilayer feedforward neural network trained by error backpropagation algorithm With high prediction accuracy and the ability to learn nonlinear relationships between data, the model is more interpretable.…”
Section: Documentmentioning
confidence: 99%